Public policies and private investment - Helliwell, John F. (Oxford : Clarendon P., 1968)
This study attempts to develop a coherent view of the investment process in order to analyze the effects of a number of monetary and fiscal policies designed to influence investment by corporations.
Includes bibliographical references p. [225]-232 and index.
hza 02/08/2018
Loans
Keywords: Capital investments; Monetary policy; Fiscal policy